Perception towards Rewards in Digital Traditional Games: Experience from Pilot Study - Azzah Abu Bakar, Nur; Che Pa, Noraziah; Fazillah Hibadullah, Cik; Hussain, Azham (International Journal of Engineering and Technology, 2018)
Rewards, in games context is something that is given in recognition of playerâ€™s achievement. Despite the importance of rewards in games engagement, the existing digital traditional games are still lacking of rewards. Hence, this study aims to introduce and incorporate rewards in Congkak, one of the Malaysian digital traditional games. In order to meet this objective, an existing Congkak was enhanced by adding rewards in a form of credits that can be redeemed. A total of 40 respondents were involved in the experiment to measure playersâ€™ perception towards rewards. The enhanced version of Congkak was demonstrated to the respondents before they were allowed to gain game experience by experimenting with the apps. Their perception towards rewards were captured through a systematic interview conducted during the experiment by using a self-constructed questionnaire. The questionnaire consists of 6 constructs that measure playersâ€™ perception in terms of the importance of rewards, motivation, survival, engagement and time rewards are needed.Â The findings reveal a positive perception towards rewards with regard to when they are needed, their importance, and their role in motivating the players and helping them to survive and keep playing the game. Hence, future development of traditional games should include rewards as a means to engage users to the games.Â Â